Evaluation of the toxicity characteristics of two industrial wastes valorized by geopolymerization process (2015)
This paper evaluates the toxicity associated with two industrial wastes used as raw material of geopolymers. These wastes are fly ash (FA) and spent catalyst catalytic cracking (FCC). The residues were characterized using techniques such as XRF, XRD, SEM and laser granulometry. Two geopolymers systems based on FA-100% and FCC-100% were produced using SiO2/Al2O3 molar ratios of 6,0 and 2,4 and Na2O/SiO2 of 0,20 and 0,25 respectively. The technique TCLP (Toxicity Characteristic Leaching Procedure) was applied in order to evaluate the toxicity. Cr, V, Zn, Ni, As, Ba, Sr, Pb and Cd elements were analyzed. The results indicate that concentrations of heavy metals leachate (except V and As) are low compared with the environmental standards. The geopolymers studied are considered effective in terms of inmobilizing contaminants.